2018
DOI: 10.1161/atvbaha.118.310945
|View full text |Cite
|
Sign up to set email alerts
|

Association of Total and Differential Leukocyte Counts With Cardiovascular Disease and Mortality in the UK Biobank

Abstract: Among circulating leukocyte subpopulations, neutrophil count in men was most consistently associated with fatal and nonfatal CVD. Further studies of interventions that lower circulating neutrophils, such as canakinumab, are required to investigate causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 39 publications
4
66
2
Order By: Relevance
“…Several previous studies have reported that WCC was associated with mortality even after adjusting for smoking 1 5 7–12. This is not fully consistent with our analysis in healthy population.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Several previous studies have reported that WCC was associated with mortality even after adjusting for smoking 1 5 7–12. This is not fully consistent with our analysis in healthy population.…”
Section: Discussioncontrasting
confidence: 68%
“…A few studies have shown that WCC or subtype is an independent predictor of mortality after controlling for potential confounding, for example, smoking 1 5 7–12. This conclusion, however, might conflict with the fact that the WCC is influenced by many factors, such as infection, inflammation, smoking and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][30][31][32] Higher neutrophil counts are associated with cardiovascular disease in men. 15 TA B L E 2 Estimated changes from baseline in the circulating numbers of total leukocytes, platelets, and erythrocytes as well as the absolute and relative counts of the leukocyte subtypes for testosterone dose groups in the 5aR trial .004…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there are no randomized trial data on the effects of exogenous testosterone on circulating leukocytes and platelets. Because of the known association of increased leukocyte [15][16][17][18] and platelet counts [19][20][21] with cardiovascular and thromboembolic risk, these findings, if confirmed in human studies, could affect the safety of testosterone treatment. These findings could also provide important clues to the site of testosterone's action in the bone marrow.…”
Section: Suppression Of Endogenous Testosterone Secretion Throughmentioning
confidence: 93%
“…Therefore, it has been generally considered that a biomarker, or a panel of biomarkers, reflecting the inflammatory and prothrombotic actions in the arterial wall, would be a highly valuable complement to the lipid biomarkers. A broad number of blood‐based biomarkers have been investigated, and not unexpectedly, several have shown an association with CVD and the risk of acute atherothrombotic events . These range from white blood cell counts (leucocytes, neutrophils) to soluble markers such as chemokines (MCP‐1), cytokines (IL‐6, IL‐18), acute‐phase proteins (CRP, serum amyloid A) and autoantibodies against specific molecular epitopes in LDL particles, such as phosphatidylcholine and apo‐B‐100 peptide sequences.…”
Section: Biomarkers For Cvd and Atherosclerosis: Current State And Nementioning
confidence: 99%